1982
DOI: 10.1002/smj.4250030407
|View full text |Cite
|
Sign up to set email alerts
|

Diversification strategy and profitability

Abstract: Prior work has shown an association between diversification strategy and profitability. This paper replicates that association using more recent and complete data and goes on to investigate the sources of the association. Theoretical arguments are advanced which predict the association which will remain once the effects of varying industry profitability are removed. Empirical tests verify this prediction and permit the discrimination between the effects of industry and diversification strategy on profitability. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
631
3
85

Year Published

1986
1986
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,030 publications
(744 citation statements)
references
References 8 publications
25
631
3
85
Order By: Relevance
“…However, while synergy and diversification have been intensively discussed in other areas, such as in the strategy literature (Amihud & Lev, 1981;Christensen & Montgomery, 1981;Rumelt, 1982;Palepu, 1985;Robins & Wiersema, 1995;Farjoun, 1998;Miller, 2004;Tanriverdi & Venkatraman, 2005), there is hardly any mention of synergies of IS investments in the IS literature.…”
Section: Neglected Disaggregation Of Is Investmentsmentioning
confidence: 99%
“…However, while synergy and diversification have been intensively discussed in other areas, such as in the strategy literature (Amihud & Lev, 1981;Christensen & Montgomery, 1981;Rumelt, 1982;Palepu, 1985;Robins & Wiersema, 1995;Farjoun, 1998;Miller, 2004;Tanriverdi & Venkatraman, 2005), there is hardly any mention of synergies of IS investments in the IS literature.…”
Section: Neglected Disaggregation Of Is Investmentsmentioning
confidence: 99%
“…Examining market entries with U.S. Census data between 1987 and 1992, Bryce and Winter (2009) found that the baseline hypothesis was not supported when two existing measures of relatedness are used. Busija, O'Neill, and Zeithaml (1997: 324) hypothesized that the mode of entry and the type of diversification proposed by Rumelt (1982) (relatedconstrained, related-linked, and unrelated) should not be correlated, and found no significant correlation between the two. Moreover, the pairwise correlation between entry mode and relatedness has been statistically insignificant in studies that 142 G. K. Lee and M. B. Lieberman have reported such correlations.…”
Section: Hypothesis 1a (Baseline Hypothesis): the Less Related A New mentioning
confidence: 99%
“…Moreover, our arguments and findings hold implications for the strategic management literature, particularly the diversification literature. For example, consider the debate on diversification and performance (beginning with Rumelt, 1974;Bettis, 1981;Christensen & Montgomery, 1981;Rumelt, 1982). In their critique of Rumelt (1974) Christensen and Montgomery (1981) argued that the relatedness/performance link in (an updated version of) Rumelt's sample was strongly influenced by industry characteristics: Controlling for such characteristics largely eliminated Rumelt's (1974) finding of a positive relatedness/performance link.…”
Section: Relevancementioning
confidence: 99%